The role of green strategy formulation in green behavior for municipal corporations – Analytical study - حسين, يعرب عدنان; عبد الله, سلوان ظافر (Journal of Economics and Administrative Sciences, 2020)
The research shows the importance of orientation towards the formulation of the green strategy and its effect in determining the behavior of the green municipal institution in Babel governorate. The research highlighted the formulation of the green strategy as an important variable, especially today, the trend towards protecting the environment and minimizing the damage resulting from the delivery of services, and through it also the type of green behavior or performance adopted by the municipal institution and the emergence of the need for a strategy that is not harmful to the environment. The research took the sample intentionally comprehensive size of 222 personnel of municipal institutions and some formations concerned with the planning and diversity of personnel specialization and included technical, administrative and legal specialties and various levels of responsibility and academic achievement within the Ministry of Housing, Construction, Municipalities, the Ministry of Planning and the Babylon Provincial Council. The research tool was a questionnaire distributed to the research sample, which appeared homogeneous and not scattered by the answers to what was put in the questionnaire on the search variables, which included several sub-dimensions each. The research concluded the most important results, which included the formulation of the green strategy and dimensions such as follow-up and the extent of the participation of management and organization and changes in business models and even financial revenues expected from the adoption of a green strategy.